2018
DOI: 10.1038/s41598-018-25348-1
|View full text |Cite
|
Sign up to set email alerts
|

Apple procyanidins promote mitochondrial biogenesis and proteoglycan biosynthesis in chondrocytes

Abstract: Apples are well known to have various benefits for the human body. Procyanidins are a class of polyphenols found in apples that have demonstrated effects on the circulatory system and skeletal organs. Osteoarthritis (OA) is a locomotive syndrome that is histologically characterized by cartilage degeneration associated with the impairment of proteoglycan homeostasis in chondrocytes. However, no useful therapy for cartilage degeneration has been developed to date. In the present study, we detected beneficial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Furthermore, the apples were rich in epicatechin, caffeoyl glucoside, and a procyanidin trimer. Based on tentative structure elucidation in the present study and literature descriptions, this trimer is suggested being procyanidin C1 [65].…”
Section: Qualitative and Quantitative Determination Of Phenolic Composupporting
confidence: 54%
“…Furthermore, the apples were rich in epicatechin, caffeoyl glucoside, and a procyanidin trimer. Based on tentative structure elucidation in the present study and literature descriptions, this trimer is suggested being procyanidin C1 [65].…”
Section: Qualitative and Quantitative Determination Of Phenolic Composupporting
confidence: 54%
“…The effect of Apple polyphenols have already been correlated to beta-oxidation (mainly peroxisomal) and to regulation of FA metabolism [50]. Mice fed a diet containing apple polyphenols present increased levels of mRNA coding for PPAR-α and PPAR-γ, two genes involved in lipid metabolism [51].…”
Section: Discussionmentioning
confidence: 99%
“…Apple polyphenols from immature apples, compounds composed of several polyphenols, exert anti-allergy, anti-fatigue and life-extending effects ( 26 , 150 ). Masuda et al investigated the role of apple polyphenols in protecting chondrocytes and improving OA ( 26 ). Their findings showed that apple polyphenols could enhance mitochondrial biogenesis by promoting the integrity of mtDNA and mitochondrial fusion through AMPK/SIRT1/PGC-1α signaling.…”
Section: Exogenous Drugs To Optimize Mitochondria In Oamentioning
confidence: 99%
“…Moreover, apple polyphenols could promote proteoglycan biosynthesis. In an in vivo study, apple procyanidins protected against articular cartilage degeneration and prevented the development of knee OA in chondrocyte-specific Sod2-/- mice ( 26 ). Based on these results, we can conclude that apple polyphenols may be potential drugs for treating OA.…”
Section: Exogenous Drugs To Optimize Mitochondria In Oamentioning
confidence: 99%